2003
DOI: 10.1071/rd02048
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide dismutase affects the viability of thawed European mouflon (Ovis g. musimon) semen and the heterologous fertilization using both IVF and intracytoplasmatic sperm injection

Abstract: Abstract. This study evaluated the effects of superoxide dismutase (SOD) on viability and acrosome integrity of European mouflon spermatozoa after cryopreservation and on the fertilization rates of sheep oocytes after IVF or intracytoplasmatic sperm injection (ICSI). Frozen semen was thawed and washed with synthetic oviduct fluid supplemented with 0.6% bovine serum albumin. After centrifugation, the spermatozoa pellet was split into two culture systems: (i) without SOD; and (ii) in the presence of 1500 IU mL −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
(45 reference statements)
1
11
0
2
Order By: Relevance
“…Extenders can be supplemented with antioxidants before freezing (Peña et al 2003(Peña et al , 2004Gadea et al 2005a;Roca et al 2005;Fernández-Santos et al 2007), or just after thawing (Berlinguer et al 2003;Gadea et al 2005b;Fernández-Santos et al 2009a), which block the production of reactive oxygen species or counteract oxygen toxicity. We have demonstrated that some antioxidants improve the cryopreservation of red deer epididymal spermatozoa (Fernández-Santos et al 2007), and, using ascorbic acid, we could mimic the protective effect of the epididymal environment ).…”
Section: Introductionmentioning
confidence: 99%
“…Extenders can be supplemented with antioxidants before freezing (Peña et al 2003(Peña et al , 2004Gadea et al 2005a;Roca et al 2005;Fernández-Santos et al 2007), or just after thawing (Berlinguer et al 2003;Gadea et al 2005b;Fernández-Santos et al 2009a), which block the production of reactive oxygen species or counteract oxygen toxicity. We have demonstrated that some antioxidants improve the cryopreservation of red deer epididymal spermatozoa (Fernández-Santos et al 2007), and, using ascorbic acid, we could mimic the protective effect of the epididymal environment ).…”
Section: Introductionmentioning
confidence: 99%
“…, 2004, 2005; Fernández‐Santos et al. , 2007), or just after thawing (Berlinguer et al. , 2003; Gadea et al.…”
Section: Introductionmentioning
confidence: 99%
“…No studies have been published on the effects of antioxidant addition to freezing diluents on red deer epididymal spermatozoa freezability. Several antioxidants have been tested that either scavenge ROS directly or counter the effects of ROS toxicity in the semen of a variety of mammalian and avian species; these include vitamin E (Brigelius‐Flohe and Traber, 1999), vitamin C (O et al, 2006), butylated hydroxytoluene (BHT) (Donoghue and Donoghue, 1997), catalase (Roca et al, 2005), and superoxide dismutase (Berlinguer et al, 2003; Roca et al, 2005).…”
mentioning
confidence: 99%